Analisis Perilaku Menabung Masyarakat di Kota Surabaya - Leony Puspitasari, Cindy; Amrullah Suwaidi, Rahman (Jurnal Riset Pendidikan Ekonomi, 2025)
Saving is a strategic endeavor to enhance an individual's future financial stability. When individuals develop an awareness of the importance of saving, they will be better equipped to allocate their resources more wisely, leading to sustainable financial benefits over time. This study investigates the influence of financial attitudes, lifestyle choices, and self-control on the saving behavior of residents in Surabaya City. Using a quantitative design, this study utilizes a Likert scale to assess these variables. Data was collected through simple random sampling method, resulting in 180 participants. Hypothesis testing was conducted using the Partial Least Squares (PLS) approach with the help of SmartPLS software. The findings of the study explain that financial attitudes, lifestyle, and self-control contribute to shaping savings behavior in individuals living in Surabaya